Manajemen Rekrutmen Penerimaan Peserta Didik Baru Dalam Meningkatkan Mutu Lulusan DI SMA Walisongo Sragen Jawa Tengah - Khonaah, Khonaah; Widiastuti, Nur; Setyaningsih, Rina; Zulkarnain , Iskandar (Innovative: Journal Of Social Science Research, 2024)
This research aims to explore and analyze the recruitment management of new student admissions at Walisongo Sragen High School as an effort to improve the quality of graduates. Secondary education has a crucial role in shaping the character and skills of students, and an effective recruitment process can be the key to success in achieving this goal. The research results show that a well-planned recruitment strategy can improve the quality of incoming new students, as well as influence the quality of graduates. The use of information technology and social media is also an important factor in achieving efficiency and effectiveness in the recruitment process. Apart from that, parental involvement in the recruitment process can have a positive impact on students' academic and non-academic development during their study period at Walisongo High School, Sragen. This research contributes to schools improving recruitment management strategies, including the use of technology and parental involvement as an integral part of the process. In this way, it is hoped that Walisongo Sragen High School can produce quality graduates, ready to face global challenges, and make a positive contribution to society.